Analysis of Barahoi Dance Forms in Kuala Tungkal Regency - Raflesia Meirina (Proceeding International Conference on Malay Identity, 2020)
Barahoi dance is an art form that exists in the people of Kuala Tungkal, Jambi. This Barahoi dance is danced by 10 male dancers and 10 female dancers. This dance is inspired by seeing a fisherman who is catching fish for his daily needs. The movement of the Barahoi dance depicts the sharpness and agility of a fisherman, among the movements of the Kaia dance are: footstep, left and right steps, ducking. These movements are processed and stylized into a work of art, namely the Barahoi dance. The musical instruments used in this dance are: Malay drum, violin, gong, accordion and gandang muko duo. Meanwhile, the costumes used in this dance performance are clothes for brackets and songket cloth along with tengkuluk for female dancers and batik clothes, basic pants, sarongs and tanjak for male dancers. Keywords: analysis; form; barahoi dance